Anna May Wong : from laundryman's daughter to Hollywood legend - Hodges, Graham Russell, 1946- (Hong Kong University Press, HKU, 2012)
Anna May Wong was perhaps the best known Chinese American actresses during Hollywood's golden age, a free spirit and embodiment of the flapper era much like Louise Brooks. She starred in over fifty movies between 1919 and 1960, sharing the screen with such luminaries as Douglas Fairbanks Sr. and Marlene Dietrich. Born in Los Angeles in 1905, Wong was the second daughter of six children born to a laundryman and his wife. Obsessed with film at a young age, she managed to secure a small part in a 1919 drama about the Boxer Rebellion. Her most famous film roles were in The Thief of Baghdad, Old Sa.